Research of labor conflictsin the enterprise - Tyufanov, G. L.; Pererva, P. G. (Національний технічний університет "Харківський політехнічний інститут", 2023)
It is substantiated that the basis of the mechanism for resolving labor disputes in Ukraine is the use of the principle of conciliation procedures through the relevant commissions and labor arbitrations. However, despite the work carried out by these bodies, a systematic solution to the problem of settling collective labor disputes (conflicts) has not yet been practically implemented.
Дослідження трудових конфліктів на підприємстві
Keywords: conflicts; labor collective; psychology; personnel management; enterprises